2002
DOI: 10.1136/ip.8.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a child safety program based on the WHO Safe Community model

Abstract: Objectives: To evaluate the outcome of the World Health Organization (WHO) Safe Community model with respect to child injuries. Study design: A population based quasiexperimental design was used. Cross sectional pre-implementation and post-implementation data were collected in intervention (Motala municipality) and control (Mjölby municipality) areas, both in Östergötland county, Sweden. Results: The total relative risk of child injury in the intervention community decreased more (odds ratio 0.74; 95% confiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 16 publications
0
41
0
3
Order By: Relevance
“…56,57 School-and community-based programs that yield improvement in safety practices by parent safety education, home inspection, and the distribution of safety supplies seem to improve knowledge and behavior related to injury prevention and decrease the risk for injury. [58][59][60] Our study, although population based and the largest to date in the United States, has several important limitations. The numerator data were obtained from a trauma registry, which contains only data on patients who had significant injuries and were seen in an ED or hospitalized.…”
Section: E548 Femur Fractures Associated Injuries Sociodemographic mentioning
confidence: 97%
“…56,57 School-and community-based programs that yield improvement in safety practices by parent safety education, home inspection, and the distribution of safety supplies seem to improve knowledge and behavior related to injury prevention and decrease the risk for injury. [58][59][60] Our study, although population based and the largest to date in the United States, has several important limitations. The numerator data were obtained from a trauma registry, which contains only data on patients who had significant injuries and were seen in an ED or hospitalized.…”
Section: E548 Femur Fractures Associated Injuries Sociodemographic mentioning
confidence: 97%
“…For instance, Sacks et al (Sacks et al, 1992) noted that safety rounds were ineffective, whereas Bjärås et al (Bjärås et al, 1990) found that safety rounds eliminated risk factors in a public environment. Lindqvist et al (Lindqvist et al, 2002) included safety rounds in their Safe Community concept. In worksite safety promotion, safety rounds are perceived as effective (Menckel et al, 1996).…”
Section: Study Population and Designmentioning
confidence: 99%
“…Ao se analisar os centros afiliados ao centro colaborador da OMS para a promoção da segurança comunitária e a rede de comunidades seguras 4 , observa-se uma alta concentração de programas em países nórdicos (16), seguidos pela Austrália (quatro), Canadá (três), outros países europeus (quatro) e países asiáticos (três). A ausência de programas em países em desenvolvimento pode ser decorrente da rigidez na composição dos crité-rios de inclusão no conceito de comunidade segura, onde vários trabalhos, baseados nos princípios da promoção da saúde, poderiam estar incluídos.…”
Section: Discussionunclassified
“…E, ainda, tratando-se da segurança da criança, os autores observaram que, nas famílias que sofreram intervenção, houve uma melhora, estatisticamente significante, no controle de substâncias venenosas, assim como na utilização de assentos apropriados para crianças nos carros. Trata-se, portanto, de um estudo em que, embora baseado na comunidade e, de certa forma, trabalhe com os conceitos de comunidade segura, os indicadores de violência doméstica e de outras Tabela 1 -Estudos de programas de prevenção de injúrias não intencionais, baseados na comunidade, tendo menores de 18 anos como público alvo Coggan et al 14 Lindqvist et al 19 Lindqvist et al 16 Waitakere Redução da incidência total de lesões em relação ao controle, sem significância estatísti-ca. O efeito observado foi mais importante para as injúrias moderadas.…”
Section: Síntese Dos Dados: Prevenção De Injúrias Intencionaisunclassified